CITRUS BUTANOL ESTERS HAVING PLASTICIZING AND LUBRICANT CHARACTERISTICS OBTAINED IN A BUBBLE COLUMN TYPE REACTOR - BORAN, Sorina; MOSOARCA, Giannin; NITU, Sabina; VANCEA, Cosmin (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The aim of this paper was the synthesis of some citric esters with potential biodegradable properties and their use as plasticizers or PVC lubricants. Citric esters were obtained in a bubbling column-type esterification reactor, using citric acid as the acid component, and monoethylene glycol, n-butanol, t-butanol as the hydroxyl components. The esters were characterized by FT-IR spectrometry to reveal the existence of the esteric bonds. Esters present a good thermal stability. The TCS criterion shows a level of compatibility specific to secondary plasticizers. There is a similarity between the values of the tested compounds and the standard DOF regarding hardness. The breaking strength are better and the values of elongation at break are close to the considered standards. The esters prove a very good migration towards rubber and are comparable to tribological fluids. The four balls test showed that without additives and at a test level of 40 daN for 60 min time period, the diameters of the wear spot are generally very good, being in the range of 0.43-0.62 mm. By adding oils, their behavior improves. The welding load values are also good (200-220 daN). The synthesized citrus esters have clear characteristics of plasticizers and/or lubricants for PVC.